ANALISIS PERHITUNGAN METODE KONVENSIONAL DAN METODE ABC DALAM MENENTUKAN TARIF JASA BONGKAR MUAT INTERNASIONAL PADA TERMINAL PETI KEMAS PT PELABUHAN INDONESIA III (PERSERO) SEMARANG - Faizal Satria Desitama; Poniman Poniman; Rustono Rustono (Politeknik Negeri Semarang, 2015)
Calculation of the cost of goods at first applied in manufacturing companies, but in its development calculation of the cost of service has been adapted by the service company, which is called the cost of services. The cost service have a very important role in determining the price of services.If calculation the cost of services is too low indeed will attract consumers, but led to the sale of services can not cover the cost of production of services, and otherwise, if the cost of services is too high, then the resulting selling price is too expensive, it will result in product and services less attractive to consumers. This study aims to determine differences in rates Unloading International Container if calculated by the conventional method and the Activity based costing system method, The conventional method imposes a costs arising from rates International loading unloading using the basic costs allocation of volume services production. while the ABC method is a method of determining the cost of using the activity and cost driver as a means to calculate the cost of International loading unloading. The research result for Unloading unloading International Container FCL 20’ and Container 20' using Conventional methods are respectively 80.68 and 60.69. Whereas calculations using the ABC method has a tariff of 74.80 and 56.27, while rates by the company is also around 80 and 60. The results Shows, Terminal Peti Kemas Semarang (TPKS) does not charge rates too far from the cost, which means that although TPKS has been using its own method in determining the service rates loading unloading of containers, but it already covers the entire needs of the cost of loading unloading. However, by using the ABC method, TPKS can appropriately plan budget in detail. ABC method can also provide information of production costs that is more accurate and informative.